2006
DOI: 10.1080/01926230500512076
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and Mechanisms of Drug-Induced Vascular Injury in Non-Rodents

Abstract: In preclinical safety studies, drug-induced vascular injury can negatively impact candidate-drug selection because there are no obvious diagnostic markers for monitoring this pathology preclinically or clinically. Furthermore, our current understanding of the pathogenesis of this lesion is limited. While vasodilatation and increased shear stress appear to play a role, the exact mechanism(s) of injury to the primary target cells, smooth muscle (SMC) and endothelial cell (EC), are unknown. Evaluation of potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 68 publications
0
39
0
Order By: Relevance
“…demonstrated that animals given either 60 or 240 mg/kg ZD6169 showed increases in plasma vWF of more than 60% of prestudy values, as early as 1.5 hr post-dosing that remained at 6 hr and gradually declined below pre-study levels thereafter to 24 hr post dose. and Newsholme et al (2000) have suggested that vWF plasma levels fall quickly post-dosing due to several possible causes, and the conclusions of these latter publications and those of and Louden et al (2006) were that vWF plasma levels alter due to numerous stimuli, are rapidly transient, and thus render this molecule inappropriate for use as a specific biomarker of DIVI. However, we have demonstrated in our studies that its presence within plasma makes it a useful diagnostic indicator of plasma penetration into damaged arteries caused by ZD6169 and ZD1611.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that animals given either 60 or 240 mg/kg ZD6169 showed increases in plasma vWF of more than 60% of prestudy values, as early as 1.5 hr post-dosing that remained at 6 hr and gradually declined below pre-study levels thereafter to 24 hr post dose. and Newsholme et al (2000) have suggested that vWF plasma levels fall quickly post-dosing due to several possible causes, and the conclusions of these latter publications and those of and Louden et al (2006) were that vWF plasma levels alter due to numerous stimuli, are rapidly transient, and thus render this molecule inappropriate for use as a specific biomarker of DIVI. However, we have demonstrated in our studies that its presence within plasma makes it a useful diagnostic indicator of plasma penetration into damaged arteries caused by ZD6169 and ZD1611.…”
Section: Discussionmentioning
confidence: 99%
“…Kerns et al 2005; C. Louden et al 2006;Newsholme et al 2000;Stagliano et al 2001;Thomas et al 2009;Thomas et al 2012;Turk 2010;Weaver et al 2008;Zhang et al, 2002b;Zhang et al 2006;2012). The majority of candidate biomarkers have included factors involved in EC activation , edema, inflammation, tissue remodeling, (Blake, and Ridker 2001;Dalmas et al 2008;Daguès, Pawlowski, Guigon, et al 2007;) and maintenance of vascular tone (C. Louden et al 2006). The search for DIVI markers has been formalized, with the formation of a collaborative consortium of industry, academic, and regulatory experts into The Predictive Safety Testing Consortium (PSTC) Vascular Injury Working Group (VIWG), and a panel of biomarkers for DIVI has been proposed (Mikaelian et al 2014).…”
Section: Biomarkers Of Biotherapeutic-associated Divimentioning
confidence: 99%
“…These have included circulating proteins, and even genomic markers, but their utility has been limited by their potential qualification with only a very limited number of compounds, most of which are vasoactive molecules (Brott et al 2005;, Daguès, Pawlowski, Guigon, G, et al 2007Dalmas et al 2008Dalmas et al , 2011Enerson et al 2006;Joseph, Rees, and Dayan 1996;W. Kerns et al 2005; C. Louden et al 2006;Newsholme et al 2000;Stagliano et al 2001;Thomas et al 2009;Thomas et al 2012;Turk 2010;Weaver et al 2008;Zhang et al, 2002b;Zhang et al 2006;2012). The majority of candidate biomarkers have included factors involved in EC activation , edema, inflammation, tissue remodeling, (Blake, and Ridker 2001;Dalmas et al 2008;Daguès, Pawlowski, Guigon, et al 2007;) and maintenance of vascular tone (C. Louden et al 2006).…”
Section: Biomarkers Of Biotherapeutic-associated Divimentioning
confidence: 99%
See 2 more Smart Citations